Dinamika Psikologis Anak Pelaku Kejahatan Seksual - Rochmah, Khoirunita Ulfiyatun; Nuqul, Fathul Lubabin (Jurnal Psikologi Tabularasa, 2015)
This research aimed to know the psychological dynamics of child sex offenders. This research wasÂ social psychology. Method of Â the research was qualitative method with phenomenological strategy. Participatns were 5 children from LP Anak Kelas II A Blitar. Participants Â were sexual offenders. Results from this study show that child sex offenders due to factors impulse or peer support, teenage sex drive increases, and with a broken family relationships.